ANALISIS PENGGUNAAN CANVA SEBAGAI MEDIA PEMBELAJARAN PADA PESERTA DIDIK MATA PELAJARAN IPAS DI SEKOLAH DASAR - Khalidah Aurora; Frida Destini; Amrina Izzatika; Fadhilah Khairani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Science education in elementary schools still faces challenges in understanding abstract material and a lack of engaging instructional media, making technology-based innovations such as Canva necessary. This study aimed to analyze the use of Canva as an instructional medium for the IPAS subject in the fourth grade at UPT SD Negeri 1 Pringsewu Selatan, with teachers and students as the research subjects. This study focused on four sub-focuses: ease of use, interactivity, learning motivation, and material relevance. The research employed a qualitative method using a case study approach, with data collection conducted through observation, interviews with the school principal, teachers, and students, as well as documentation. The results indicated that the use of Canva had a positive impact and supported the science learning process in Grade IV. Furthermore, regarding the first sub-focus, operational ease showed positive results in Grade IV. Second, Canva’s interactivity demonstrated that its use enhanced students’ active participation during science lessons. Third, learning motivation related to Canva showed a positive increase among students. Fourth, the relevance of Canva’s content indicated that the material presented aligned with learning objectives and was closely related to daily life.